Compulsory drug detention center experiences among a community-based sample of injection drug users in Bangkok, Thailand - Zhang Ruth; Suwannawong Paisan; Fairbairn Nadia; Hayashi Kanna; Kaplan Karyn; Csete Joanne; Wood Evan; Kerr Thomas (BMC, 2011)
Abstract Background Despite Thailand's official reclassification of drug users as "patients" deserving care and not "criminals," the Thai government has continued to rely heavily on punitive responses to drug use such as "boot camp"-style compulsory "treatment" centers. There is very little research on experiences with compulsory treatment centers among people who use drugs. The work reported here is a first step toward filling that gap. Methods We examined experiences of compulsory drug treatment among 252 Thai people who inject drugs (IDU) participating in the Mitsampan Community Research Project in Bangkok. Multivariate logistic regression was used to identify factors independently associated with a history of compulsory treatment experience. Results In total, 80 (31.7%) participants reported a history of compulsory treatment. In multivariate analyses, compulsory drug detention experience was positively associated with current spending on drugs per day (adjusted odds ratio [AOR] = 1.86; 95%CI: 1.07 - 3.22) and reporting drug planting by police (AOR = 1.81; 95%CI: 1.04 - 3.15). Among those with compulsory treatment experience, 77 (96.3%) reported injecting in the past week, and no difference in intensity of drug use was observed between those with and without a history of compulsory detention. Conclusion These findings raise concerns about the current approach to compulsory drug detention in Thailand. Exposure to compulsory drug detention was associated with police abuse and high rates of relapse into drug use, although additional research is needed to determine the precise impact of exposure to this form of detention on future drug use. More broadly, compulsory "treatment" based on a penal approach is not consistent with scientific evidence on addressing drug addiction and should be phased out in favor of evidence-based interventions.